Chirality from Cryo-Electron Tomograms of Nanocrystals Obtained by Lateral Disassembly and Surface Etching of Never-Dried Chitin - Bai, Long; Kämäräinen, Tero; Xiang, Wenchao; Majoinen, Johanna; Seitsonen, Jani; Grande, Rafael; Huan, Siqi; Liu, Liang; Fan, Yimin; Rojas, Orlando J. (ACS nano, 2020)
The complex nature of typical colloids and corresponding interparticle interactions pose a challenge in understanding their self-assembly. This specifically applies to biological nanoparticles, such as those obtained from chitin, which typically are hierarchical and multidimensional. In this study, we obtain chitin nanocrystals by one-step heterogeneous acid hydrolysis of never-dried crab residues. Partial deacetylation facilitates control over the balance of electrostatic charges (ζ-potential in the range between +58 and +75 mV) and therefore affords chitin nanocrystals (DE-ChNC) with axial aspect (170-350 nm in length), as determined by cryogenic transmission electron microscopy and atomic force microscopy. We find that the surface amines generated by deacetylation, prior to hydrolysis, play a critical role in the formation of individual chitin nanocrystals by the action of a dual mechanism. We directly access the twisting feature of chitin nanocrystals using electron tomography (ET) and uncover the distinctive morphological differences between chitin nanocrystals extracted from nondeacetylated chitin, ChNC, which are bundled and irregular, and DE-ChNC (single, straight nanocrystals). Whereas chitin nanocrystals obtained from dried chitin precursors are known to be twisted and form chiral nematic liquid crystals, our ET measurements indicate no dominant twisting or handedness for the nanocrystals obtained from the never-dried source. Moreover, no separation into typical isotropic and anisotropic phases occurs after 2 months at rest. Altogether, we highlight the critical role of drying the precursors or the nanopolysaccharides to develop chirality.
Created from Fastlane, Scopus look-up
Keywords: chirality; chitin nanocrystals; cryo-TEM; electron tomography; surface deacetylation; twist